2014
DOI: 10.1039/c3py01270k
|View full text |Cite
|
Sign up to set email alerts
|

New dialkoxyamine-trithiocarbonate for the synthesis of multiblock copolymers through in tandem RAFT/NMP

Abstract: A new strategy for synthesizing multiblock copolymers comprising polystyrene, polyacrylates, poly(N-isopropylacrylamide), etc. is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
(27 reference statements)
0
17
0
Order By: Relevance
“…Similar counterintuitive changes in SEC retention times upon block extension, though likely due to yet another mechanism, have been reported by St Thomas et al during the characterization of a range of triand multiblock copolymers based on the temperature-responsive polymer poly(N-isopropylacrylamide) (PNIPAM) prepared via reversible deactivation radical polymerization (RDRP) techniques (entries 10-12 in Table 1). 39 4), with an associated ∼40% apparent reduction in the molecular weight from M n = 23 000 g mol −1 to 14 000 g mol −1 . This work 39 does not contain comparative values from, for instance, NMR or mass spectrometry (MS).…”
Section: Review Polymer Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar counterintuitive changes in SEC retention times upon block extension, though likely due to yet another mechanism, have been reported by St Thomas et al during the characterization of a range of triand multiblock copolymers based on the temperature-responsive polymer poly(N-isopropylacrylamide) (PNIPAM) prepared via reversible deactivation radical polymerization (RDRP) techniques (entries 10-12 in Table 1). 39 4), with an associated ∼40% apparent reduction in the molecular weight from M n = 23 000 g mol −1 to 14 000 g mol −1 . This work 39 does not contain comparative values from, for instance, NMR or mass spectrometry (MS).…”
Section: Review Polymer Chemistrymentioning
confidence: 99%
“…39 4), with an associated ∼40% apparent reduction in the molecular weight from M n = 23 000 g mol −1 to 14 000 g mol −1 . This work 39 does not contain comparative values from, for instance, NMR or mass spectrometry (MS). The authors point out that both PNIPAM and PPEGA are known to be strongly susceptible towards hydrogen bonding (although the latter can only accept and not donate H-bonds).…”
Section: Review Polymer Chemistrymentioning
confidence: 99%
“…Water was deionized before use (Purelab Classic UV, Elga LabWater). RAFT/NMP ( I ) dual chain transfer agent was synthetized as reported …”
Section: Methodsmentioning
confidence: 99%
“…The chain-end functionalization of homopolymers and triblock copolymers prepared in solution departing from I was clearly demonstrated in our recent paper. 22 Here we showed that the alkoxyamine end-group of poly(acrylic acid) blocks can keep their integrity during the RAFT chain extension reaction (Scheme 2) with hydrophobic monomers if the temperature (80 °C) is kept below the cleavage temperature of the considered TEMPO-based alkoxyamines (ca 120°C). Consequently, latex particles as shown in Scheme 1 containing trithiocarbonate moieties (green dots) in their hydrophobic core and PAA chains end-capped with alkoxyamines (yellow dots) as hydrophilic shell.…”
Section: Surfactant-free Emulsion Raft Polymerization (Step 2)mentioning
confidence: 98%